ASPEK SOSIAL DALAM NOVEL HELLO KARYA TERE LIYE: PENDEKATAN SOSIOLOGI SASTRA - Alfindra, Rivaldi Fikhri; Rahmat, Dicky Pauji; Kurnia, Kurnia (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research aims to describe and social aspects contained in the novel Hello by Tere Liye. This research uses a qualitative descriptive method. The data produced in the form of words in the form of quotations, obtained by reading, marking, and classifying techniques. Data collection in this research uses library techniques. Data analysis is done by reading the novel Hello and marking certain parts that describe the social characteristics that appear in the book. Then draw conclusions and provide solutions based on the findings of the analysis. The results showed that Tere Liye's Hello depicts a striking social contrast between two characters. One of the characters is the daughter of an elite family, representing a highly privileged social group. On the other hand, the other character is described as a young man with a casual appearance, messy hair, and dark skin, possibly representing a disadvantaged social group, even as a manual laborer.